2001
DOI: 10.1038/labinvest.3780213
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation of the RB1 Gene in Glioblastomas

Abstract: SUMMARY:Loss of expression of the retinoblastoma gene (RB1) has been shown to occur in up to 25% of glioblastomas (WHO Grade IV). To elucidate the underlying mechanism, we assessed RB1 promoter hypermethylation using methylation-specific polymerase chain reaction and RB1 expression by immunohistochemistry in 35 primary (de novo) glioblastomas and in 21 secondary glioblastomas that had progressed from low-grade diffuse astrocytoma (WHO Grade II) or anaplastic astrocytoma (WHO Grade III). Promoter hypermethylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
2
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(103 citation statements)
references
References 26 publications
7
91
2
3
Order By: Relevance
“…26 Sodium bisulfite modification was Novel tumor suppressor loci on 22q12.3 in secondary glioblastoma M Nakamura et al performed using a CpGenomet DNA Modification Kit (Intergen, Oxford, UK) according to the manufacturer's protocol with minor modifications. 8,27,28 The primer sequences, with methylated and unmethylated PCR and MSP conditions, have been previously reported. 29 Amplified products were electrophoresed on 2% agarose gels and visualized by ethidium bromide staining.…”
Section: Methylation-specific Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Sodium bisulfite modification was Novel tumor suppressor loci on 22q12.3 in secondary glioblastoma M Nakamura et al performed using a CpGenomet DNA Modification Kit (Intergen, Oxford, UK) according to the manufacturer's protocol with minor modifications. 8,27,28 The primer sequences, with methylated and unmethylated PCR and MSP conditions, have been previously reported. 29 Amplified products were electrophoresed on 2% agarose gels and visualized by ethidium bromide staining.…”
Section: Methylation-specific Pcrmentioning
confidence: 99%
“…1 Recent genetic analyses have shown that these glioblastoma subtypes develop through different genetic pathways; 2-4 primary glioblastomas occur in older patients characterized by EGFR amplification/overexpression, PTEN mutation, homozygous p16 INK4a deletion, and loss of heterozygosity (LOH) throughout chromosome 10, 3,5,6 while secondary glioblastomas develop in younger patients and typically show frequent p53 mutations, LOH preferentially on chromosomes 10q and 19q, 3,[5][6][7] and promoter methylation of the RB1 gene. 8 LOH on 22q seems to be of interest, since this allelic loss is a common event in gliomas, occurring with a frequency varying between 11 and 39%. Interestingly, 22q LOH appears to be uncommon in low-grade astrocytomas, but is more frequently detected in anaplastic astrocytomas and glioblastomas.…”
mentioning
confidence: 99%
“…Experimental data have shown that in vitro methylation of the RB1 promoter region reduced pRB expression. 28 Unilateral retinoblastoma and some brain tumors show loss of pRB expression which is associated with aberrant methylation of the CpG island within the RB1 promoter region; [29][30][31] however, the methylation status of the RB1 gene in soft-tissue sarcoma has not been described. RB1 promoter hypermethylation was detected in four out of 27 (14.8%) dedifferentiated components, whereas no hypermethylation was detected in any of the well-differentiated components.…”
Section: Discussionmentioning
confidence: 99%
“…/RB1 jest ważny dla procesu proliferacji, ponieważ białko RB1 podobnie jak białko TP53 reguluje cykl komórkowy, kontrolując przejście z fazy G1 do fazy S. Zaburzenia tego szlaku występują zarówno w pierwotnym, jak i we wtórnym GBM [77,78] i polegają na delecji P16…”
Section: Polish Versionunclassified